Evaluation of influence of incisal guidance on the force exerted at the maximum possible intercuspal position and in protrusion - An In vivo study - Samdisha S Lulla; Raghavendra Adaki; Aditi Samant; Shridevi Adaki; Swateja Surwase; Shruti Pardesi (Wolters Kluwer Medknow Publications, 2023)
Aim: Incisal guidance (IG) varies with maxillary and mandibular teeth wear. It in turn governs the forces on adhesive restorations. The present study evaluates the variation in forces because of changes in IG. Materials and Methods: IG was recorded on 46 subjects along with the distance from centric contact to incisal edge. Biteforce was recorded in the maximum possible intercuspal position (MIP) and in protrusion in the anterior region. Data analysis was performed using SPSS Version 21 at a confidence level ≤0.05. Pearson correlation test was applied to determine r value. Results: The association between forces on anterior teeth in MIP and forces on teeth in contact in protrusion is statistically significant (P value 0.001). There is definitive correlation between forces exerted in MIP and the distance travelled from centric contact to incisal edge (r = 0.059). There is a weak correlation between forces on anterior teeth in MIP and protrusive IG (r value 0.172). Conclusion: The force on anterior teeth in MIP with steeper IG is higher. Hence, the restoration margin should be kept away from the centric contact point.